2023
DOI: 10.1002/mp.16246
|View full text |Cite
|
Sign up to set email alerts
|

Compensation cycle consistent generative adversarial networks (Comp‐GAN) for synthetic CT generation from MR scans with truncated anatomy

Abstract: Background MR scans used in radiotherapy can be partially truncated due to the limited field of view (FOV), affecting dose calculation accuracy in MR‐based radiation treatment planning. Purpose We proposed a novel Compensation‐cycleGAN (Comp‐cycleGAN) by modifying the cycle‐consistent generative adversarial network (cycleGAN), to simultaneously create synthetic CT (sCT) images and compensate the missing anatomy from the truncated MR images. Methods Computed tomography (CT) and T1 MR images with complete anatom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…The cycleGAN requires the fake image to keep all the information in the original image, as a result, its CT correction ability was reduced in some degree. Compared with previous studies, the results of Zhao et al [ 6 ] showed the average MAE, PSNR, and SSIM calculated over test patients were 91.3 HU, 27.4 dB, and 0.94 for the proposed Comp-cycleGAN models trained with body-contour information. However, our cycleSimulationGAN model scored better on the three quantitative metrics with MAE (60.88), PSNR (36.23), and SSIM (0.985).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The cycleGAN requires the fake image to keep all the information in the original image, as a result, its CT correction ability was reduced in some degree. Compared with previous studies, the results of Zhao et al [ 6 ] showed the average MAE, PSNR, and SSIM calculated over test patients were 91.3 HU, 27.4 dB, and 0.94 for the proposed Comp-cycleGAN models trained with body-contour information. However, our cycleSimulationGAN model scored better on the three quantitative metrics with MAE (60.88), PSNR (36.23), and SSIM (0.985).…”
Section: Discussionmentioning
confidence: 63%
“…Magnetic resonance imaging (MRI) has become an essential imaging modality in both staging and targets volume (TV) delineation for head and neck (H&N) cancer radiotherapy (RT) owing to its intrinsically superior soft-tissue contrast, functional information, high resolution and non-radiation [ 1 3 ]. Precise contouring is crucial when treating H&N cancer patients presenting with primary soft tissue invasion or subtle intra-cranial invasion for accurate dose delivery to TV, and consequently improve the treatment outcomes [ 4 6 ]. Several studies have proven that MRI was more accurate than Computer Tomography (CT) and Positron Emission Tomography (PET) and was even closer to the pathological specimen measurements considered the “gold standard”, which can also substantially decrease the inter-observer variability of TV and organs at risks (OARs) delineation [ 1 , 2 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…SO) does not considerably affect the contouring performance. Although we have identified considerable contouring differences for specific OARs, we can conclude that almost all OARs can be contoured with a similar degree of variability in either the CT or MR modality, which provides favorable support for MR images from the perspective of MR-only [38][39][40] and MR-guided RT. 42,43…”
Section: Discussionmentioning
confidence: 71%
“…However, because of the often insufficient CT image contrast for soft tissues, several studies recommended the integration of complementary magnetic resonance (MR) modality. 4,33 This is important especially from the perspective of OAR contouring, 4,34,35 synthetic MR image generation for MR-aided RT, 36,37 synthetic CT image generation for MR-only RT [38][39][40][41] and MR-guided RT. 42,43 While some OARs can be accurately and reliably contoured in CT images (i.e., bone structures such as, e.g., the mandible), MR images are often used to better visualize soft tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic Magnetic Resonance (sMR) images (Approach 5) were generated by a pre-trained, in-house developed Comp-GAN 22 . To improve the structural consistency between the sMR and input CT images, a structure-consistency loss was introduced in the cycleGAN model 22 , 23 .…”
Section: Methodsmentioning
confidence: 99%